2008
DOI: 10.1002/bjs.6105
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of randomized controlled trials on the safety and effectiveness of day-case laparoscopic cholecystectomy

Abstract: Background: Although day-case laparoscopic cholecystectomy can save bed costs, its safety has to be established. The aim of this meta-analysis is to assess the advantages and disadvantages of day-case surgery compared with overnight stay in patients undergoing elective laparoscopic cholecystectomy.Methods: Randomized clinical trials addressing the above issue were identified from The Cochrane Library trials register, Medline, Embase, Science Citation Index Expanded and reference lists. Data were extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(92 citation statements)
references
References 53 publications
3
78
0
11
Order By: Relevance
“…Laparoscopic cholecystectomy performed safely in an ambulatory setting has become widely popular and accepted [19,20]. Our LOS was primarily 1-2 days, with more than half of the patients discharged in the ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy performed safely in an ambulatory setting has become widely popular and accepted [19,20]. Our LOS was primarily 1-2 days, with more than half of the patients discharged in the ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the available evidence relating to the safety of day-case LC, little is known as to the feasibility of its introduction in the UK population. 8 Our day-case unit had never performed a laparoscopic procedure prior to the commissioning of this service. The provision of adequate staff education and training prior to full LC introduction is essential to the success of the service.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in anaesthetics and increased surgeons laparoscopic experience have encouraged surgeons to perform LC as an elective outpatient procedure with only a few hours' hospital stay post-surgery. Many studies and literature reported the effectiveness and safety of ambulatory LC in selected patients, with reduced cost and high level of patient satisfaction [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%